Targeting potassium channels for increasing delivery of imaging agents and therapeutics to brain tumors - Ningaraj, Nagendra S.; Khaitan, Divya (Frontiers in Pharmacology, 2013)
Every year in the US, 20,000 new primary and nearly 200,000 metastatic brain tumor cases are reported. The cerebral microvessels/ capillaries that form the blood–brain barrier (BBB) not only protect the brain from toxic agents in the blood but also pose a significant hindrance to the delivery of small and large therapeutic molecules. Different strategies have been employed to circumvent the physiological barrier posed by blood-brain tumor barrier (BTB). Studies in our laboratory have identified significant differences in the expression levels of certain genes and proteins between normal and brain tumor capillary endothelial cells. In this study, we validated the non-invasive and clinically relevant Dynamic Contrast Enhancing-Magnetic Resonance Imaging (DCE-MRI) method with invasive, clinically irrelevant but highly accurate Quantitative Autoradiography (QAR) method using rat glioma model. We also showed that DCE-MRI metric of tissue vessel perfusion-permeability is sensitive to changes in blood vessel permeability following administration of calcium-activated potassium (BKCa) channel activator NS-1619. Our results show that human gliomas and brain tumor endothelial cells that overexpress BKCa channels can be targeted for increased BTB permeability for MRI enhancing agents to brain tumors. We conclude that monitoring the outcome of increased MRI enhancing agents’ delivery to microsatellites and leading tumor edges in glioma patients would lead to beneficial clinical outcome.